Mycoremediation of Synthetic Azo Dyes by White-Rot Fungi Grown on Diary Waste: A Step toward Sustainable and Circular Bioeconomy - Irene Gugel; Daniela Summa; Stefania Costa; Stefano Manfredini; Silvia Vertuani; Filippo Marchetti; Elena Tamburini (Fermentation, 2024)
This study assesses the efficacy of three white-rot fungi—Bjerkandera adusta, Phanerochaete chrysosporium, and Trametes versicolor—in degrading synthetic dyes and lignin in pulp and paper mill effluents, which annually contribute around 40,000 million cubic meters of dyed waste. Exploiting the structural resemblance of dyes to lignin, the fungi utilize ligninolytic enzymes—lignin peroxidase, manganese peroxidase, and laccase—to break down the pollutants. Initial mycoremediation trials in synthetic dye solutions with Direct black 80, Direct yellow 11, Basic brown 1, Orange II, and Red 8 BLP achieved decolorization rates of 70–80% within 7 days, except for Red 8 BLP. Both soluble and insoluble lignin fractions were significantly reduced, with an overall removal rate of 80–90%. Contrary to prior beliefs about the recalcitrance of azo dyes, B. adusta demonstrated substantial biodegradation capabilities, even on non-lignocellulosic substrates, such as dairy waste. The decolorization efficacy varied with dye structure, suggesting that efficiency should not be judged solely on color reduction. Remarkably, B. adusta also effectively decolorized and removed lignin from actual mill effluents without pH alteration, indicating a viable low-cost bioremediation strategy. This invites further investigation into optimizing B. adusta for industrial wastewater biodecolorization, especially in the field of PAHs (Polycyclic Aromatic Hydrocarbons) and EDCs (Endocrine Disrupting Chemicals).